2002
DOI: 10.1525/aeq.2002.33.1.5
|View full text |Cite
|
Sign up to set email alerts
|

The Marketization of Education: Public Schools for Private Ends

Abstract: This article argues that the neoliberal renaissance of the 1980s marketized education, with distinctly negative social consequences. We examine the emergence and promotion of a national-level discourse that positioned schools in the service of the economy. Based on ethnographic research conducted in North Carolina, we then show how local growth elite utilized this discourse to further their own race and class interests to the exclusion and detriment of poorer, African American parents and students. We suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
97
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(104 citation statements)
references
References 16 publications
0
97
0
4
Order By: Relevance
“…The core concept behind the creation of charter schools is that they are associated with business interest groups. Many recent studies have indicated that charter schools worsen educational inequality and increase the gap among different socioeconomic populations because the under-the-table selection process and the lottery system of admission ruin fairness (Bartlett et al 2002;Lipman 2003;Ravitch 2013). For example, many charter schools operate independently and autonomously, and they use a lottery process to decide enrollment by random selection.…”
Section: Socioeconomic Inequality In Public Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…The core concept behind the creation of charter schools is that they are associated with business interest groups. Many recent studies have indicated that charter schools worsen educational inequality and increase the gap among different socioeconomic populations because the under-the-table selection process and the lottery system of admission ruin fairness (Bartlett et al 2002;Lipman 2003;Ravitch 2013). For example, many charter schools operate independently and autonomously, and they use a lottery process to decide enrollment by random selection.…”
Section: Socioeconomic Inequality In Public Educationmentioning
confidence: 99%
“…Children's futures should not be determined on the basis of a simple gamble. Moreover, the growing competition for public funding between charter schools and public schools negatively affects poor districts with financial deficits (Bartlett et al 2002;Ravitch 2010;Ravitch 2013). Businesses that become involved in public education generally tend to invest in potentially profitable areas, which are the high-income and majority-White districts.…”
Section: Socioeconomic Inequality In Public Educationmentioning
confidence: 99%
“…(France, 2003), to hopes that neoliberal reform leader Michelle Rhee could save DC schools (Thomas, 2008), the mainstream media has characterized market-based reforms and charter schools as muchneeded efforts to save struggling communities of color (Hankins & Martin, 2006). Under the cover of this savior framework, the neoliberal education reform agenda has implemented projects of racialized dispossession that especially impact low-income African American communities (Buras, 2011;Lipman & Haines, 2007;Bartlett et al, 2002).…”
Section: Literaturementioning
confidence: 99%
“…Some research has shown how the charter school reform movement in New Orleans and other cities engages in a project of racialized appropriation of community assets from low-income communities of color for the accumulation of wealth by and for the privilege of White elites (Buras, 2011;Lipman & Haines, 2007;Lipman, 2004;Bartlett, Frederick, Gulbrandsen, & Murillo, 2002). This has occurred under the guise of a discursive framework (Kumashiro, 2008) claiming values of educational equity and closing racial achievement gaps.…”
Section: Literaturementioning
confidence: 99%
“…To be sure, segregation between schools is a result of many factors, including zoning and the selection policies of schools; regional and urban planning; and choice of residence and also school choice (see also Archbald, 2004;Bartlett et al, 2002;Taylor, 2009;Urquiola, 2005). Drawing zones around schools may in itself not be "class-neutral".…”
mentioning
confidence: 99%